2020
DOI: 10.1007/s42729-020-00342-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-Solubilizing Microorganisms: Mechanism and Their Role in Phosphate Solubilization and Uptake

Abstract: Phosphorus is the second most critical macronutrient after nitrogen required for metabolism, growth, and development of plants. Despite the abundance of phosphorus in both organic and inorganic forms in the soil, it is mostly unavailable for plant uptake due to its complexation with metal ions in the soil. The use of agrochemicals to satisfy the demand for phosphorus to improve crop yield has led to the deterioration of the ecosystem and soil health, as well as an imbalance in the soil microbiota. Consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(204 citation statements)
references
References 192 publications
2
130
0
8
Order By: Relevance
“…Phosphate solubilizing microorganisms (PSMs) represent microflora important to organic P mineralization, solubilizing inorganic P minerals, and storing large amounts of P in microbial biomass. Rawat et al [42] documented the diversity in PSMs in soil including over 40 bacteria, cyanobacteria, and actinomycetes and 15 fungi including several vesicular arbuscular mycorrhizae. PSMs exude phosphatase enzymes, chelates, and organic acids, with a concomitant decrease in soil pH to solubilize (oxidize) soil P into plant available Pi.…”
Section: Microbial Oxidation Of Phi To Pimentioning
confidence: 99%
“…Phosphate solubilizing microorganisms (PSMs) represent microflora important to organic P mineralization, solubilizing inorganic P minerals, and storing large amounts of P in microbial biomass. Rawat et al [42] documented the diversity in PSMs in soil including over 40 bacteria, cyanobacteria, and actinomycetes and 15 fungi including several vesicular arbuscular mycorrhizae. PSMs exude phosphatase enzymes, chelates, and organic acids, with a concomitant decrease in soil pH to solubilize (oxidize) soil P into plant available Pi.…”
Section: Microbial Oxidation Of Phi To Pimentioning
confidence: 99%
“…Arai & Sparks (2007) found that rhizosphere acidification was an effective way to help obtain mobile P from calcareous soils. Additionally, the organic acids (like citric acid, gluconic acid, oxalic acid, and tartaric acid) (Rawat et al, 2020), inorganic acids (like hydrochloric acid, sulfuric acid, nitric acid, and carbonic acid) and H 2 S production by phosphate-solubilizing microorganisms have been reported to solubilize inorganic phosphate, although inorganic acids have low efficiency compared to organic acids (Gaind, 2016). (2) The cation-anion exchange balance, organic anion and proton extrusion, which lower soil pH to dissolve insoluble phosphates.…”
Section: Utilization Of Inorganic Residual P In Soilsmentioning
confidence: 99%
“…The utilization of organic P also plays a major role in the use of soil residual P. Organic P in soils generally accounts for 20-30% of the total residual P and in some cases accounts for 95% (Rawat et al, 2020). The vast majority of soil organic P is held by a single or double lipid bond, which can be divided into inositol (mainly from plant residue), nucleic acid (from plant and soil organism residue) and phospholipid (from plant, soil animal and microbial residue) forms (Betencourt et al, 2012).…”
Section: Utilization Of Organic Residual P In Soilsmentioning
confidence: 99%
See 2 more Smart Citations